Auditors’ and PAC members’ views on performance auditing practices in Malaysia: a qualitative approach - Mat Daud, Zaidi; Fraser, Ian (Universiti Putra Malaysia Press, 2015)
This study explored the views of both auditors in the National Audit Department (NAD), and Public Accounts Committee (PAC) members toward the current performance-audit practices in the Malaysian public sector by interviewing selected members of each group. Results revealed that the views of these two groups diverged on several issues concerning auditor roles and responsibilities, auditor competence and independence, as well as the format, content and usefulness of the audit reports. The most significant divergence was in the respective views on the auditors' responsibilities for fraud detection.